"RUN, JUMP, OR SHUFFLE ARE ALL THE SAME WHEN YOU DO IT FOR THE MAN!": The OPHR, Black Power, and the Boycott of the 1968 NYAC Meet. Issue 1 (2nd January 2019) - Blackman, Dexter L.
Abstract : The article examines black activists' use of sports and protest in the 1960s to elaborate on the meaning of black advancement in the period, especially Black Power. Mainstream opponents labeled scholar-activist Harry Edwards a "black militant" for initiating the Olympic Project for Human Rights (OPHR), a black boycott campaign of the 1968 Olympics. As part of a plan to counter that repression and attract supporters and provide the OPHR a media platform, Edwards launched a boycott of the New York Athletic Club (NYAC) track meet in February 1968. While opponents and scholars concluded that Edwards's threats of violence were the primary reason the NYAC boycott succeeded, the article demonstrates that it succeeded because of the Black Power agenda of raising awareness of the need to combat "institutionalized racism." Consequently, the NYAC garnered the OPHR significant credibility and more allies and allowed Edwards to continue campaigning for an Olympic boycott. Worried opponents, however, continued to label Edwards and blacks' use of protests in sports militant. Consequently, because of the media and other opponents' dominance, the meaning of the protest against the NYAC, blacks use of protest in sports, and Black Power continue to be demonized and distorted.